H.265/HEVC frame-level bitrate allocation algorithm considering video content - Wei LI; Fu-zheng YANG; Peng REN (Tongxin xuebao)
In order to guarantee the consistency between the coded bits and target bits,a frame-level bitrate allocation al-gorithm considering the content feature was proposed for H.265/HEVC codec.The main factors to affect the output bi-trate were first discussed by the analysis of rate-distortion theory.According to the video coding principle,the related pa-rameter was then predicted to reflect the content complexity.Finally,an efficient frame-level bitrate allocation algorithm was constructed.Experimental results show that the target bits and coded bits keep a better consistency,and the recon-struction video quality is improved by 0.103 dB in average.